BALUTAN KONFUSIANISME DALAM MANUVER GEOSTRATEGI TIONGKOK DI KEPULAUAN SOLOMON MELALUI BELT AND ROAD INITIATIVE PADA TAHUN 2019-2022 - Maedy, Almasiva Tirta; Mahendra Wiswayana, Wishnu (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
This article investigates China's geostrategy in the Solomon Islands using a Relational Theory approach developed by Yaqing Qin, which is heavily inspired by Confucian community values. Unlike Western-dominated theory and approaches to geostrategy, China pursues its geostrategy by widening the circle of interactions and deepening their intimacy with other countries across the world. Therefore, relational strength becomes the primary means of China's power projection, as expressed in an inclusive and equitable economic and development strategy. This article focuses on the critical role of China's Belt and Road Initiative (BRI) as a flexible and inclusive geostrategic instrument, emphasizing mutual respect and goal alignment with the Solomon Islands. As a result, the Solomon Islands government believes that formal collaboration with China will improve national legitimacy and sovereignty. Through this relational approach, China has successfully formed an alternative international governance that is based on long-term relationships and mutually beneficial interests rather than domination and expansionist approaches to broadening its geostrategy in other countries or region.